A production and operations management study on Jolly Plastic Moulding Corporation - Baradas, Jennifer; Pe, Joanna; Rodriguez, Charmaine (Diliman, Quezon City College of Engineering, 2003)
A Production and Operations Management study was done on Jolly Plastic Moulding Corporation. The corporation is involved with the manufacture of plastic wares such as drawers, shoe racks, baskets, pails, stands, cup containers, dish drainers, etc. The study included the documentation, evaluation and analyses of the company's current production system, forecasting, capacity, inventory management, aggregate planing, scheduling and the identification of problem areas and their respective recommendations. The process documented was the production of 5-layer drawers and shoe racks from the year 2000 to the year 2002. The documentation of the operations of the system was used for evaluation and analysis. Forecasting the demand for drawers and shoe racks was accomplished through the Multiplicative Model, which is applicable where seasonality and trend is present in the demand, as in the case of of the company. Evaluation and analyses of the present system using the documentation resulted in the identification of the following problem areas: (1) high inventory level; (2) breakdown of machines; and (3) significant amount of rejects. The following recommendations were presented to solve the corresponding problem areas: (1) for high inventory level - the use of a recommended 6-month Anticipation Inventory; (2) for breakdown of machines - the implementation of a total preventive maintenance program that includes frequent check-up of the machines, monitoring of lubrication, and cleaning up of the nozzle; and (3) for the significant amount of rejects - putting up signs to remind the workers of the proper lubrication procedures, the purchase of digital timers for the manual injection molding machines, and the employment of regular maintenance on the molding machines of both drawers and the shoe racks.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Jolly Plastic Moulding Corporation; Plastics industry; Production engineering